INTIMATE FRIENDSHIP SEBAGAI SARANA MENANGGULANGI TOXIC CULTURE DI KALANGAN SISWA SMA NEGERI 2 PALANGKA RAYA - Waode Gusti Rusliana; Muslimah Muslimah; Surawan Surawan (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT This study was conducted in response to the increasing prevalence of toxic culture among school adolescents, characterized by the use of harsh language, mocking, body shaming, social exclusion, and the spread of gossip through social media. These conditions have an impact on students’ mental health and social relationships within the school environment. This study aims to analyze the forms of negative social interaction culture (toxic culture) among students, including bullying behavior, social discrimination, aggressive communication, and exclusion in social relationships, as well as to examine the role of intimate friendship in reducing such behavior at SMA Negeri 2 Palangka Raya. This study employed a descriptive qualitative approach with a field research design. The research subjects consisted of students from classes XI (3), XI (4), and an Islamic Religious Education teacher. Data were collected through observation, semi structured interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that toxic culture among students appeared in the form of harsh language, mocking, body shaming, social media insinuations, and exclusion within friendship groups. The study also found that intimate friendship plays a role in reducing such behavior through mutual trust, empathy, openness, and emotional support among peers, thereby creating more positive and harmonious social relationships within the school environment. Therefore, intimate friendship can serve as a preventive means in overcoming toxic culture and supporting the creation of a more comfortable and harmonious school environment. ABSTRAK Penelitian ini berangkat dari maraknya perilaku toxic culture di kalangan remaja sekolah yang ditandai dengan penggunaan bahasa kasar, saling mengejek, body shaming, pengucilan sosial, serta penyebaran gosip melalui media sosial. Kondisi tersebut berdampak terhadap kesehatan mental dan hubungan sosial siswa di lingkungan sekolah. Penelitian ini bertujuan untuk menganalisis bentuk-bentuk budaya interaksi sosial negatif (toxic culture) di kalangan siswa, yang mencakup perilaku perundungan, diskriminasi sosial, komunikasi agresif, dan pengucilan dalam pergaulan, serta mengkaji peran intimate friendship dalam mengurangi perilaku tersebut di SMA Negeri 2 Palangka Raya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian lapangan. Subjek penelitian terdiri atas siswa kelas XI (3), XI (4), dan guru Pendidikan Agama Islam. Teknik pengumpulan data dilakukan melalui observasi, wawancara semi terstruktur, dan dokumentasi. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa toxic culture di kalangan siswa muncul dalam bentuk penggunaan bahasa kasar, saling mengejek, body shaming, sindiran di media sosial, dan pengucilan dalam kelompok pertemanan. Penelitian ini menemukan bahwa intimate friendship berperan dalam mengurangi perilaku tersebut melalui sikap saling percaya, empati, keterbukaan, serta dukungan emosional antarteman sehingga tercipta hubungan sosial yang lebih positif dan harmonis di lingkungan sekolah. Dengan demikian, intimate friendship dapat menjadi sarana preventif dalam menanggulangi toxic culture serta mendukung terciptanya lingkungan sekolah yang lebih nyaman dan harmonis.